2022
DOI: 10.1128/spectrum.01077-21
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Metabolites in Atrial Fibrillation Patients and Their Changes after Catheter Ablation

Abstract: Gut microbiota and metabolites play a very important role in human health and can not only assess human health but also treat and prevent diseases. We analyzed the characteristics of the microbiota and metabolites in the human gut and found the effect of disease on gut microbiota and metabolites, which may be of important value in the pathogenesis of atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…It seemed that CA enriches intestinal symbiotic bacteria and reduces pathogenic bacteria. Correspondingly, metabolites, such as oleanolic acid are downregulated after ablation, while citrulline is increased (24). This also emphasizes the crucial role of gut microbiota in AF pathogenesis.…”
Section: The Relationship Between Intestinal Flora With the Incidence...mentioning
confidence: 83%
See 1 more Smart Citation
“…It seemed that CA enriches intestinal symbiotic bacteria and reduces pathogenic bacteria. Correspondingly, metabolites, such as oleanolic acid are downregulated after ablation, while citrulline is increased (24). This also emphasizes the crucial role of gut microbiota in AF pathogenesis.…”
Section: The Relationship Between Intestinal Flora With the Incidence...mentioning
confidence: 83%
“…Beside AF, treatment of AF is also associated with altered gut microbiome. A recent study compared gut microbiota composition in AF patients prior to catheter ablation (CA), 2 days post CA and 1 month post CA (24). Compared with preoperative condition, 6 bacterial genera (Prevotella, Lactobacillus, Sutterella, Alistipes, Parabacteroides, and Streptococcus) enriched and 3 genera (Blautia, Ruminococcus_gnavus_group, and Anaerostipes) remarkably decreased 2 days after CA.…”
Section: The Relationship Between Intestinal Flora With the Incidence...mentioning
confidence: 99%
“…A cohort study observed that patients with atrial fibrillation and control groups shared 1,189 operational taxonomic units (OTUs). Within them, 897 specific OTUs were observed exclusively in patients having atrial fibrillation, whereas only 477 were observed only in controls [ 58 ].…”
Section: Reviewmentioning
confidence: 99%
“…Haemophilus , Alistipes , Enterococcus , Weissella , Parabacteroides , Megamonas , Streptococcus , and Klebsiella were in high concentration in patients with atrial fibrillation. Agathobacter concentrations were observed to be higher in the control group [ 58 ].…”
Section: Reviewmentioning
confidence: 99%
“…Another mechanism through which microbiota can promote the development of HF is atrial fibrillation [ 87 ], which is associated with a high concentration of Proteobacteria , Actinobacteria and Firmicutes , Streptococcus , Haemophilus , Alistipes , Enterococcus , and Klebsiella [ 88 ]. Gram-negative lipopolysaccharides (LPS) are endotoxins able to trigger NLRP3 inflammasomes with consequent caspase-1 activation and the production of IL-1β and IL-18.…”
Section: Gut Microbiota Composition and Hfmentioning
confidence: 99%